Paparan informasi kesehatan reproduksi melalui media pada perilaku seksual pranikah: analisis data SDKI tahun 2012 - Puspasari Puspasari; Sukamdi Sukamdi; Ova Emilia (Berita Kedokteran Masyarakat (BKM), 2017)
The correlation of reproductive health information exposure from media on premarital sexual behaviour: an Indonesia demographic health survey 2012 analysisPurposeThis study aimed to determine the correlation of type and intensity of exposure of reproductive health information through media to the sexual behavior of adolescents and young adults in Indonesia.MethodsThis study used a cross-sectional design. The data used was the Indonesian sub-survey of adolescent reproductive health, Indonesia demographic and health survey.ResultsThe results showed that adolescents and young adults who receive the health information type of adolescent reproductive health category have a smaller prevalence in sexual intercourse before marriage than information of contraceptive methods category or both. The intensity of exposure to reproductive health information which was low or no exposure, have higher prevalence of premarital sexual behavior. Age, gender, level of education, level of wealth, smoking, drinking alcohol, drug consumption and dating intimacy are significantly associated with premarital sexual behavior of adolescents and young adults.ConclusionType and intensity of reproductive health information are significantly associated with premarital sexual behavior of adolescents and young adults. The high intensity of exposure and type of adolescent reproductive Health category have a smaller prevalence in sexual intercourse before marriage.